Highly Reversible Cycling of Zn‐MnO2 Batteries Integrated with Acid‐Treated Carbon Supportive Layer (Small Methods 2/2022). Issue 2 (17th February 2022) - Kim, Byung Gon; Park, Sang Wook; Choi, Hong Jun; Park, Jun‐Woo; Lee, Hongkyung; Choi, Jeong‐Hee
Abstract : Inside Back Cover In article number 2101060, Kim, Lee, and co‐workers introduce the Zn‐MnO2 cell incorporating an acid‐treated carbon support layer (aCSL) and it shows stable cycling and rate performances compared to the cell with a common porous separator, owing to the confinement of Mn 2+ between cathode and aCSL, revitalization of Mn 2+ /Mn 4+ reactions, and facilitation of zinc hydroxyl sulfate formation/decomposition by rendering extra e‐pathway.